Care, contagion, community self & other - Mussai, Renée ca. 20./21.Jh; Sealy, Mark 1960- (Autograph, 2021)
Initiated during the first national lockdown in spring 2020, Autograph commissioned 10 UK-based visual artists to create new work responding to the wider contexts of the Covid-19 crisis. Using primarily photography and film, the artists reflect carefully and critically, often very personally, on the impact of the pandemic, their lived experiences, and the inevitability of change. To contextualise these new artist commissions, we invited 10 writers - poets, scholars and curators - to produce a short essay in response, and published a series of interviews with each artist discussing their practice. Presented together in this beautifully designed book, the texts and artist commissions offer thoughtful reflections on changing conditions of existence: generous invitations to contemplate what it means to be human, and how we might care for one another. Featuring a new introductory essay by Autograph's senior curator Renée Mussai, and a Foreword by Autograph's director Mark Sealy.00Exhibition: Autograph, London, UK (23.09.2021 - 12.02.2022).
Keywords: Geschichte 2020; Kunst; COVID-19 -- Motiv; Großbritannien; Ausstellungskatalog -- Autograph -- 23.09.2021-12.02.2022 -- London